Les Bicyclettes de Belsize - Hickox, Douglas; Suschitzky, Wolfgang; Huxtable, Judy; May, Anthony; Goddard, Leslie (Optimum, 2009)
"Les Bicyclettes de Belsize" is a charmingly whimsical musical short filmed around Hampstead Village one summer, in which a man sees his ideal woman on a billboard poster and falls in love. [www.moviemail.com]
Keywords: DVD-Video